Digital Transformation in Some Countries and Its Implications for Vietnam - Huong, Nguyen Thi Lan; Rubia, Josdela Moral (Journal of Social Science and Humanities, 2025)
Digital transformation plays an important role in the development of countries as well as businesses. Digital transformation has received the attention of many countries and scholars around the world. Based on research and experience of some Asian countries (Malaysia, Thailand, China), this article mainly uses secondary data through selective inheritance of a number of studies related to digital transformation at home and abroad. From there, we provide some reference lessons for Vietnam in the process of digital transformation, as well as training on digital transformation to improve endogenous capacity and promote economic and social development.